Changes in Vietnam - China Trade in the Context of China’s Economic Slowdown - Huong, Vu Thanh; Phuong, Nguyen Thi Lan (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 35 No 2, 2019)
After three decades of maintaining high and stable GDP growth, China’s economy has shown signs of slowdown since 2012. By comparing China’s growth rates in two periods, namely 2002-2011 and 2012-2018, this paper points out evidence of China’s economic slowdown and four key reasons underlying this decline including the decrease in China’s export growth, the decrease in China’s investment efficiency, China’s transition to a new growth model and the US-China trade war. The paper then examines the changes in Vietnam’s trade with China in the context of China’s economic slowdown. The results show robust evidence that the growth rates of Vietnam’s two-way trade with China have witnessed a downward trend. Both Vietnam’s import and export growth rates reduced over the two periods but imports of Vietnam from China have more seriously suffered. In the coming time, if the Chinese economy becomes worse, especially if the US-China trade war continues escalating, the potential impacts of China’s economic decline on Vietnam’s trade with China might be more significant. In such a case,Vietnam would be more dependent on imports from China and would need to cope with more difficulties in promoting exports to China, leading to a more serious trade deficit with China. Based on these results, the paper highlights some measures to support Vietnam to deal with the possible impacts from China’s economic slowdown in the future.